Comportamiento agronomico y valoracion nutricional de tres variedades de brachiaria y panicum en ell canton pedro vicente maldonado - Viveros Ruiz, Edison Germán (2012)
Pastures and fodder are the staple food of cattle and other grazing use efficiency could meet much of the nutritional needs of cattle. This research was carried out at the "Guadalupe" Campus "United We Stand 1". In the Canton Pedro Vicente Maldonado, Pichincha Province. Established research "agronomic performance and nutritional assessment of three varieties of Brachiaria and Panicum in Canton Pedro Vicente Maldonado," where the objective is raised evaluate the agronomic and nutritional assessment of three varieties of Brachiaria and Panicum at different stages of maturity . We studied six varieties of grass (v1: Savoy common v2: Savoy tanzania, v3: Savoy tobiata; v4 B. brizantha, B. decumbens v5 and v6 Mulato, and the factor (E), three four ages of harvest: (e1 : 21; e2: 42, e3: e4 63 and 84). Design We used a randomized complete block (DCA). The greater weight of the sheet is presented in Savoy grass common to the 21 days with 159.00 g, at 42 to 63 days pasture 1264.25 and 1527.00 Tobiata with g and 84 days with grass common Savoy, 1494 75 g. Stem weight recorded the brunt in Savoy Tobiata at 21, 42, 63 days 282.50, 1527.25, and 1867.00 g, respectively, similarly to the 84 days the best results were obtained Savoy is on the grass Tanzania. The leaf: stem ratio at 21 days the highest value was registered with the grass B. Brizantha with 1.00, at 42 days showed the highest value is the grass B. Decumbens 63 days 1.67 to most leaf-stalk is on the grass B. Mulatto with 0.92 and 84 days Savoy Tobiata grass with 0.99, the longest leaf in the grass Tobiata presented with 72.55, 89.10, 95.35, and 89.65 cm in the different stages of maturity. The width of the grass blade is Tobiata stands at 21, 42, 63 and 84 days 3.50, 3.00, 3.50, 3.50 cm, respectively. The grass B. Brizantha presented in three cutting ages the highest number of leaves at 21 days 489.10, 281.30 to 742.65 for 42 days and 84 days, the grass B. Mulato at 63 days had the best results with 667.70 for the four ages.